Compact reactor architectures designed with fractals. Issue 8 (26th May 2021) - Grande, Carlos A.
Abstract : A new methodology for digital production of fractal reactors was developed and implemented. Reactors manufactured with 3D fractals offer enhanced vorticity and compactness that can lead to reduction of material used for production. Abstract : Chemical reactors are the heart of chemical and pharmaceutical plants. Tailored reactors with increased efficiency for specific applications can move industry a step forward towards a better environmental performance. Advances in manufacturing techniques expanded the possibilities to produce customized reactors. This work presents a novel methodology to design reactors based on fractal mathematics in software that is not commonly used in chemistry or chemical engineering. The designed geometry was used to predict the residence time distribution as an indicator of the reactor performance. This new approach offers the possibility to manufacture compact, efficient and customizable 2D and 3D reactors that can be coupled with ancillary equipment to enhance mass and heat transfer.